Analisis Potensi Dan Efektivitas Pemungutan Pajak Reklame Di Kota Bandung - Arry Irawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to determine the level of effectiveness of the advertising tax collection and how big is the actual potential of the advertisement tax in Bandung. The research was conducted at the Regional Revenue Management Agency of Bandung City. The method applied in this study is a quantitative descriptive method, which analyzes data and calculates the amount of potential from 2015 to 2019 along with the level of effectiveness of the collection. The types of data used in this research are quantitative data and documentation data. Quantitative data is in the form of data consisting of a series of values, numbers, while documentation data is data in the form of journals, notes, newspapers, writings or reports. In the 2019 fiscal year, the realization of Bandung City Advertising Tax receipts with the criteria of